The contribution of probiotics for the double-edge effect of cefazolin on postoperative neurocognitive disorders by rebalancing the gut microbiota - Zhang, Tianyao; Wu, Xiaochu; Liu, Bin; Huang, Han; Zhou, Cheng; Liang, Peng (Frontiers in Neuroscience, 2023)
Emerging evidence indicates that perioperative gut dysbacteria is prevalent, and can be associated with postoperative neurocognitive disorders (PND). Antibiotics and probiotics are key factors that affect the microbiota. Many antibiotics have the effects of anti-microorganisms and direct anti-inflammatory actions, which may be double-edged in terms of cognition. Activation of the NLRP3 inflammasome has been reported to be involved with cognitive deficits. The aims of this study were to detect the impact and mechanism of probiotics in affecting neurocognitive disorders related to perioperative gut dysbacteria through the NLRP3 pathway. In a randomized-control trail, adult Kunming male mice with surgery received cefazolin, FOS+probiotics, CY-09 or placebo during four separate experimental cohorts. Learning and memory were assessed by fear conditioning (FC) tests. The hippocampus and colon were harvested after FC tests to determine inflammatory response (IR) and the permeability of barrier systems, and feces were collected for 16s rRNA. Surgery/anesthesia decreased the freezing behavior 1 week after surgery. Cefazolin attenuated this declination but aggravated postoperative freezing behavior 3 weeks after surgery. Probiotics ameliorated surgery/anesthesia-induced memory deficits and perioperative cefazolin-induced postoperative memory deficits at 3 weeks after surgery. NLRP3, caspase-1, Interleukin-1β(IL-1β) and Interleukin-18(IL-18) levels were increased 1 week after surgery in the hippocampus and colon, which were attenuated by CY-09 and probiotics, respectively. Both surgery/anesthesia stress and only cefazolin induced dysbacteria and IR, which could be restored by probiotics. These results suggest that probiotic is an efficient and effective method to maintain the balance of gut microbiota, which may attenuate NLRP3-related inflammation and ameliorate PND.